2012
DOI: 10.1016/j.regpep.2012.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(3–4) counteracts the Angiotensin II inhibitory action on renal Ca2+-ATPase through a cAMP/PKA pathway

Abstract: We recently demonstrated that Angiotensin-(3-4) [Ang-(3-4)], an Ang II-derived dipeptide, overcomes inhibition of plasma membrane Ca(2+)-ATPase promoted by nanomolar concentrations of Ang II in basolateral membranes of renal proximal tubule cells, with involvement of a so far unknown AT(2)R-dependent and NO-independent mechanism. The present study investigates the signaling pathway triggered by Ang-(3-4) that is responsible for counteracting the inhibitory effect of Ang II, and attempts to elucidate the functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…In this regard, the huge increase in PKA-mediated phosphorylation of PMCA in the CM group compared to the lesser increase in PKC-mediated phosphorylation (Figure 6B and 6D) could account for this imbalance. We demonstrated that PKA is a key activator of PMCA in the innervated faces of electrocytes from Electrophorus electricus L. [31] and in renal cells [28,29], whereas PKC acts as an inhibitor [41], and the undernutrition-induced imbalance between these two kinases could account for an altered Ca 2+ handling. To date, it has not been demonstrated that SERCA is a substrate for PKA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the huge increase in PKA-mediated phosphorylation of PMCA in the CM group compared to the lesser increase in PKC-mediated phosphorylation (Figure 6B and 6D) could account for this imbalance. We demonstrated that PKA is a key activator of PMCA in the innervated faces of electrocytes from Electrophorus electricus L. [31] and in renal cells [28,29], whereas PKC acts as an inhibitor [41], and the undernutrition-induced imbalance between these two kinases could account for an altered Ca 2+ handling. To date, it has not been demonstrated that SERCA is a substrate for PKA.…”
Section: Discussionmentioning
confidence: 99%
“…Kinase-mediated phosphorylation of Ca 2+ -ATPase in homogenized vas deferens tissue was determined as previously described [28,29]. The membranes (1 mg/ml) were preincubated for 10 min at 37 o C in a reaction medium containing 50 mM Hepes-Tris (pH 7.4), 0.5 mM ouabain, 5 mM MgCl 2 , 10 mM NaN 3 , 10 mM NaF, 0.3 mM EGTA, 0.34 mM CaCl 2 (10 µM free Ca 2+ ) and 1.1 M hydroxylamine in the absence of protein kinase inhibitors, or in the presence of either 10 nM PKAi 5-24 (to block PKA activity) or 10 nM calphostin C (to ensure inhibition of the diacylglycerol-dependent PKC isoforms).…”
Section: Methodsmentioning
confidence: 99%
“…The authors suggest that both receptors are required for this ultra‐sensitive response, which fits with identification of functional heterodimers between AT 1 and AT 2 receptors (Axelband et al, ). The ultra‐sensitive Ang II inhibition of Ca 2+ ‐ATPase activity was also abolished by ultra‐low concentrations of an Ang II metabolite, Ang‐(3–4) (Axelband et al, ). In fact, 10 fM Ang‐(3–4) completely restored normal Ca 2+ ‐ATPase activity via a Gα s –cAMP–PKA pathway (Axelband et al, ).…”
Section: Ultra‐sensitive Gpcr Signalling: Evidence For Angiotensin Rementioning
confidence: 99%
“…Thus, opposing phosphorylation of the Ca 2+ ‐ATPase (by Ang II–PKC or Ang‐(3–4)–PKA) in response to ultra‐low concentrations of angiotensin ligands controls its activity. Interestingly, the ultra‐sensitive Ang‐(3–4) response appeared to be dependent on the AT 2 receptor only, as it was blocked in the presence of the AT 2 receptor antagonist, PD123319, but unaffected by the AT 1 receptor antagonist, losartan (Axelband et al, ). The AT 2 receptor was found to co‐immunoprecipitate with Gα s proteins under basal conditions (Axelband et al, ).…”
Section: Ultra‐sensitive Gpcr Signalling: Evidence For Angiotensin Rementioning
confidence: 99%
See 1 more Smart Citation